Review of forms of corrosion and mitigation techniques: A visual guide - Christopher Ikechukwu Ekeocha; Bede Ikenna Onyeachu; Ini-Ibehe Nabuk Etim; Emeka E. Oguzie (African Scientific Reports)
Over the years, issues relating to corrosion have been a serious challenge confronting effective scientific and engineering applications of metallic materials in the industry. Annual loss due to corrosion issues has been quite alarming as it runs into trillions of dollars. In this review, forms of corrosion, factors affecting each form, mechanism of formation, and different aggressive environments that propagate corrosion have been identified. Mitigation techniques against this threat were all discussed, especially those involving the use of eco-friendly, cheap, available, and non-toxic materials. It was observed that the principle, process, and conditions governing each form of corrosion must be well understood before it can be effectively mitigated. This can be done either by proper material selection and design, environmental measures, modification and engineering design, modification of corrosive media, use of inhibitors, or sacrificial and protective coatings. However, adequate knowledge of the environment and nature of metal to be deployed in such an environment is essential in ensuring such material's protection, safety, and durability. For efficient and effective corrosion prevention and control, these mitigation techniques can either be implored exclusively or collectively depending on the material's nature and the setting in which it will be used.